The effect of spatial proximity to cities on rural vulnerability against flooding: An indicator based approach. (November 2020) - Jamshed, Ali; Birkmann, Joern; Ahmad Rana, Irfan; Feldmeyer, Daniel
Graphical abstract: Highlights: Vulnerability-proximity nexus framework link city proximity with rural vulnerability. Greater distances from a city increase rural exposure and susceptibility to flooding. Capacities of rural households decrease with the increase in distance from a city. Livelihood vulnerability is lower for rural settlements located closer to cities. Proximity to cities fosters better exchange of services that increases the capacity. Abstract: Vulnerability to environmental hazards has widely been assessed in disaster risk science and climate change literature by integrating socio-economic and geographical features of a community or a place. However, the role of spatial proximity to cities – an important geographical feature – in influencing household vulnerability has not been scrutinized. This paper assesses how distance to cities affects the vulnerability of rural farming communities against flood hazard. This paper proposes a Vulnerability-Proximity Nexus (VPN) framework and operationalises it in the context of Pakistan. A household survey was conducted to collect primary data from three flood-affected sub-districts of Punjab province. A total of 325 samples were collected, out of which 164 samples were from villages located near to the cities and 161 were far from the cities. Vulnerability indices were developed through holistic (exposure, susceptibility, and capacity) and livelihood (human, social, financial, physical, and natural) perspective of vulnerability. Mann-Whitney U and Pearson's correlation tests were performed to analyse linkages between distance and vulnerability. Results confirmed that the distance to the cities influences the vulnerability of surrounding farming communities. A significant and positive correlation between distance to city and rural livelihood vulnerability was found. Rural farming communities living close to the cities were less vulnerable, mainly due to better transfer of services and facilities from cities, which has also made rural communities more educated, informed, financially strong, and connected with easier access to public and private institutions. This study highlights the importance of regional and rural development discourse for vulnerability and can help disaster managers and planners to establish synergies for designing effective disaster risk reduction policies and strategies.